Selective Detection of NO2 Using Cr-Doped CuO Nanorods - Kang-Min Kim; Hyun-Mook Jeong; Hae-Ryong Kim; Kwon-Il Choi; Hyo-Joong Kim; Jong-Heun Lee (Sensors, 2012)
CuO nanosheets, Cr-doped CuO nanosheets, and Cr-doped CuO nanorods were prepared by heating a slurry containing Cu-hydroxide/Cr-hydroxide. Their responses to 100 ppm NO2, C2H5OH, NH3, trimethylamine, C3H8, and CO were measured. For 2.2 at% Cr-doped CuO nanorods, the response (Ra/Rg, Ra: resistance in air, Rg: resistance in gas) to 100 ppm NO2 was 134.2 at 250 °C, which was significantly higher than that of pure CuO nano-sheets (Ra/Rg = 7.5) and 0.76 at% Cr-doped CuO nanosheets (Ra/Rg = 19.9). In addition, the sensitivity for NO2 was also markedly enhanced by Cr doping. Highly sensitive and selective detection of NO2 in 2.2 at% Cr-doped CuO nanorods is explained in relation to Cr-doping induced changes in donor density, morphology, and catalytic effects.